2023
DOI: 10.1371/journal.pone.0280383
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition leads to the progression of coronary artery calcification in hemodialysis patients

Abstract: Background Malnutrition is considered a risk factor for cardiovascular disease in patients with chronic kidney disease. However, no in vivo studies have reported on using optical coherence tomography to evaluate the effect of nutritional status on coronary atherosclerosis in hemodialysis patients. We aimed to conduct a detailed analysis of the effect of nutritional status on the coronary arteries in hemodialysis patients. Methods Among 64 hemodialysis patients who underwent percutaneous coronary intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…These findings suggest that these factors may contribute to the development and progression of acute coronary syndromes in CKD patients. Consistent with a study by Okabe et al (2023), which investigated the impact of nutritional status on the development of coronary atherosclerosis in CKD patients, the current findings highlight the notable correlation between malnutrition and the progression of coronary artery calcification [22]. However, unlike the results of the index study, a recent cohort study (Rhee et al, 2020) reported a high prevalence of uremic symptoms among CKD patients in the United States, indicating the need for further investigation into the relationship between uremic syndrome and acute coronary events [23].…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that these factors may contribute to the development and progression of acute coronary syndromes in CKD patients. Consistent with a study by Okabe et al (2023), which investigated the impact of nutritional status on the development of coronary atherosclerosis in CKD patients, the current findings highlight the notable correlation between malnutrition and the progression of coronary artery calcification [22]. However, unlike the results of the index study, a recent cohort study (Rhee et al, 2020) reported a high prevalence of uremic symptoms among CKD patients in the United States, indicating the need for further investigation into the relationship between uremic syndrome and acute coronary events [23].…”
Section: Discussionsupporting
confidence: 92%
“…The volume of calcified plaques and calcified nodules was higher in the malnourished state, while the volume of lipid plaques was lower. The analysis revealed that low nutritional status and serum phosphorus levels were independent predictors of progression of calcified plaques [95].…”
Section: Protein-energy Malnutritionmentioning
confidence: 99%
“…Most publications on malnutrition and atherosclerosis focus on patients with chronic renal failure, including those on dialysis [94][95][96]. A study by Okabe et al confirmed that malnutrition leads to the progression of coronary artery calcification in hemodialysis patients.…”
Section: Protein-energy Malnutritionmentioning
confidence: 99%
“…2 Relationship between malnutrition, inflammation, cardiovascular disease, and mortality in chronic kidney disease Patients with CKD exhibit a higher prevalence of cardiovascular disease (CVD) and increased mortality than those without CKD (6). In a study by Okabe et al, the influence of nutritional conditions on coronary atherosclerosis was investigated in patients undergoing hemodialysis (HD) using optical coherence tomography (7). Their findings revealed that malnourished patients exhibited larger calcified plaques in affected areas at baseline and demonstrated a more significant change in calcified plaque angle in unaffected areas after 6 months.…”
Section: Introductionmentioning
confidence: 99%